Ballad for a mad girl - Wakefield, Vikki (Melbourne, Australia : Text Publishing Company, 2017)
As part of a feud between two local high schools, Grace Foley accepts the dangerous challenge to investigate the twenty-year-old mystery of missing girl Hannah Holt.
Keywords: Missing persons -- Fiction; High schools -- Fiction; Schools -- Fiction; Mystery and detective stories